Specific bearing strength of bolted composite joint with different glass fiber reinforcement - Othman, A.R. (Asian Research Publishing Network, 2016)
Bolted joints are vastly used in many applications and constitute an integral part of structural components. The reliability of the bolted joints depends mainly on the local laminate bearing strength, which is significantly influenced by various parameters. This paper presents the experimental study on the effect of different reinforcement and geometrical designs of glass reinforced composite on the bearing strength of a double-lap, single bolt joint under tensile load. Four different types of glass fibre reinforcements were prepared, consisting of chopped strand with weight of 600 g/m2, plain weave of 800 g/m2 and 290 g/m2 and 2/2 twill weave of 200 g/m2. The composite coupons were designed with a series of width to bolt diameter (W/D) and edge distance to bolt diameter (E/D) ratios, varied as 2, 3, 4 and 5 and 1, 2, 3, 4 and 5, respectively. A bearing test was conducted according to the ASTM standard D5961/D5961M-10 to determine the specific bearing strength of the laminates. It was found that the plain weave of 800 g/m2 single-bolted laminates provided highest specific bearing strength compared to other composites. The critical point of the geometric parameters by which the failure mode changes from shear-out and net-tension mode to bearing mode was also identified. The laminates with large geometric parameters failed mainly in the desired bearing failure. The analysis specifically considers the significant influence of the geometrical and material parameters on improving the structural performance of the composite bolted joints. Â©2006-2016 Asian Research Publishing Network (ARPN).